Corporate governance does any size fit? - Lehman, Cheryl R. (Advances in public interest accounting ;, 2005)
Paradigms, intellectual insights, and buzzwords have always reflected and informed social practices and have provided impetus and rationalization for macro policies. Corporate Governance has become a recent manifestation, creating interplays of political, private, academic, cultural, and economic consequences. This issue of Advances in Public Interest Accounting offers provocations challenging the received views of Corporate Governance, illuminating the controversies and ethical outcomes of using it as a prescription for public action. Whether, how, and why Corporate Governance provides innovation, mystification, or creative participation for diverse populations with diverse interests is examined in this issue. With an eclectic group of academics representing a wide range of countries, perspectives, narratives, and themes, Volume 11 provides the space for creating new sensibilities for advocating for the public interest.